2019
DOI: 10.1002/ente.201900343
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Perovskite Crystallization in Printed Mesoscopic Perovskite Solar Cells

Abstract: Additives are frequently used to enhance material properties. The addition of the processing additive 5‐aminovaleric acid iodide (5‐AVAI) into printed mesoscopic perovskite solar cells is shown to have a strong impact on the device performance and stability. Although it is difficult to understand the impact of 5‐AVAI as a processing additive by examining only the final thin films, the evolution of morphology with and without 5‐AVAI reveals that 5‐AVAI influences the crystallization behavior of the perovskite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Although these inorganic additives often produce smaller diameter crystals, the smaller crystallite size is not itself responsible for the observed performance enhancement. The smaller crystal diameters are instead indicative of crystal growth inhibition during the early stages of infiltration, which benefits stack filling through preventing the formation of blockages [125].…”
Section: Inorganic Additivesmentioning
confidence: 99%
“…Although these inorganic additives often produce smaller diameter crystals, the smaller crystallite size is not itself responsible for the observed performance enhancement. The smaller crystal diameters are instead indicative of crystal growth inhibition during the early stages of infiltration, which benefits stack filling through preventing the formation of blockages [125].…”
Section: Inorganic Additivesmentioning
confidence: 99%
“…Among various techniques, time‐resolved grazing incidence wide‐angle X‐ray scattering (GIWAXS) is a mature and powerful one to study the structural transitions occurring in perovskite materials during printing, spin coating and during temperature annealing. [ 25–27 ] Poister et al monitored changes in the formation of crystalline phase under varying process conditions in real‐time during film growth by X‐ray diffraction and revealed the importance of post annealing treatment. [ 22 ] Hu et al revealed the material transformation pathways and the morphology formation mechanism of Pb‐based perovskites from precursor solution to polycrystalline films over relevant temperature and time scales by using 2D grazing incidence x‐ray diffraction (2D‐GIXD).…”
Section: Introductionmentioning
confidence: 99%
“…This large range in performance indicates that this process is extremely irregular. All these devices were produced with the 5-AVAI additions identified by Filonik et al [ 25 ], giving improved wettability and material backfilling. The variability shown in the filling of the mesoporous scaffold exhibited here occurred despite the improved infiltration and wettability of the 5-AVAI perovskites [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly due to difficulties in the preparation of perovskite samples for cross-section observations at high magnification. Traditionally, a standard fracture method such as cutting samples in the ambient environment or in nitrogen is adequate for imaging planar cells and has been used for sample preparation [ 24 , 25 ]. This is a very simple technique, involving the scribing of a trench at the bottom of the glass substrate followed by fracturing using compressive forces on either side of the mechanically weakened area.…”
Section: Introductionmentioning
confidence: 99%